2022
DOI: 10.1097/iae.0000000000003448
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Deep Learning-Based Algorithm for Segmentation of the Ellipsoid Zone on Optical Coherence Tomography Images of an Ush2a-Related Retinal Degeneration Clinical Trial

Abstract: Purpose: To assess the generalizability of a deep learning-based algorithm to segment the ellipsoid zone (EZ).Methods: The dataset consisted of 127 spectral-domain optical coherence tomography volumes from eyes of participants with USH2A-related retinal degeneration enrolled in the RUSH2A clinical trial (NCT03146078). The EZ was segmented manually by trained readers and automatically by deep OCT atrophy detection, a deep learning-based algorithm originally developed for macular telangiectasia Type 2. Performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The results of this study demonstrate that automatic EZ area measurements generated from our DL models were in excellent agreement with those by the manual grading of the reading center, with a correlation coefficient >0.99 for both U-Net model and hybrid models as well as with a mean difference ± SD of -0.137 ± 1.131 mm 2 and -0.082 ± 0.825 mm 2 for the original (RP240) and the improved (RP340) hybrid model, respectively. Our findings are consistent with a recent study by Loo et al ( 26 ) showing a close agreement of EZ area estimates between a deep learning-based algorithm and experienced human graders (a mean DSC ± SD of 0.79 ± 0.27, a mean absolute different ± SD of 0.62 ± 1.41 mm 2 with a correlation of 0.97). The similarity between the performances of deep learning models and the manual grading for EZ area measurements suggests that deep learning may provide effective tools to significantly reduce the burden of reading centers to analyze OCT scan images in RP.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study demonstrate that automatic EZ area measurements generated from our DL models were in excellent agreement with those by the manual grading of the reading center, with a correlation coefficient >0.99 for both U-Net model and hybrid models as well as with a mean difference ± SD of -0.137 ± 1.131 mm 2 and -0.082 ± 0.825 mm 2 for the original (RP240) and the improved (RP340) hybrid model, respectively. Our findings are consistent with a recent study by Loo et al ( 26 ) showing a close agreement of EZ area estimates between a deep learning-based algorithm and experienced human graders (a mean DSC ± SD of 0.79 ± 0.27, a mean absolute different ± SD of 0.62 ± 1.41 mm 2 with a correlation of 0.97). The similarity between the performances of deep learning models and the manual grading for EZ area measurements suggests that deep learning may provide effective tools to significantly reduce the burden of reading centers to analyze OCT scan images in RP.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, image processing–based methods have been employed for automatic segmentation of outer retinal layers in RP ( 23 25 ). A more recent study by Loo et al ( 26 ) evaluated a deep learning-based algorithm originally developed for macular telangiectasia ( 27 ) for the segmentation of EZ in RP. While they showed that the DL algorithm performed well in segmenting EZ area, it doesn’t provide a measure of other photoreceptor outer segment metrics, such as volume, from OCT volume scans.…”
Section: Introductionmentioning
confidence: 99%
“…This tool reached 0.894 ± 0.102 similarity between automatic and manual grading for RP and 0.912 ± 0.055 for CHM. Loo et al also targeted EZ segmentation and validated their algorithm for macular telangiectasia in patients with USH2A -related RP, with excellent applicability (dice score 0.79 ± 0.27) [ 91 ]. Similarly, Wang et al also tested an EZ segmentation CNN in USH2A -RP and obtained a Dice score of 0.867 ± 0.105 [ 92 ].…”
Section: Selected Retinal Diseases For Which Ai-based Tools Have Been...mentioning
confidence: 99%
“…Recent advances in machine learning have provided new tools for clinical applications in ophthalmology, especially in retinal diseases [8][9][10][11][12][13][14][15]. One such application is the automated layer segmentation in OCT scan images [16][17][18][19][20][21][22][23][24], in particular automatic measurements of EZ width or area from the retinal layer segmentation of OCT scan images in patients with inherited retinal degeneration [7,[25][26][27][28]. For instance, Camino et al implemented a method based on a convolutional neural network (CNN) for the segmentation of a preserved EZ area on en face OCT in choroideremia and RP and achieved 90% accuracy [25].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Camino et al implemented a method based on a convolutional neural network (CNN) for the segmentation of a preserved EZ area on en face OCT in choroideremia and RP and achieved 90% accuracy [25]. Loo et al evaluated a deep learning-based algorithm originally developed for macular telangiectasia [29] for the segmentation of the EZ area in USH2A-related RP [26], and they showed that the deep learning algorithm performed well in segmenting the EZ area, with a dice similarity score (SD) of 0.79 (0.27). Wang et al developed a machine learning method based on random forests for the automatic detection of continuous areas of a preserved EZ in choroideremia [28].…”
Section: Introductionmentioning
confidence: 99%